THE PROFESSIONAL COMPETENCE OF THE EDUCATOR OF TODAY - Turanova Nilufar Safar qizi (Journal of new century innovations, 2024)
Annotation: This article describes the issues of modern educators having a high level of pedagogical skills, in-depth mastering of the laws of pedagogical technique (speech, face, hand, leg and body movements, facial expressions), as well as aspects of innovative competence.